Pick-and-Roll Strategies Against Switching Defense in the Endgame of EuroLeague Matches: Endgame PnR Strategies in EuroLeague Matches - Foteinakis, Panagiotis; Pavlidou, Stefania; Stavropoulos, Nikolaos (Inquiries in Physical Education and Sport, 2023)
Pick-and-roll (PnR) offense against switching defense in basketball games present an intriguing aspect for analysis. However, few studies have delved into the tactical efficacy of PnR strategies employed by the offense in the last quarter of the game. This study aimed to elucidate the offensive tactics yielding maximum advantage in PnR mismatch situations and evaluate how PnR action duration influences its effectiveness in the final quarter of closely contested EuroLeague matches. Utilizing Sport Scout observation software, four hundred PnR actions from forty EuroLeague games were observed. The observed variables included the offensive tactical action post-switch, action duration, the player concluding the action, and the outcome of the action. Chi-square (x2) analysis was employed, supplemented by the Chi-square Automatic Interaction Detector (CHAID) for data classification and predictive insights into PnR actions. The findings underscored the prevalence of switching to PnR as the primary strategy in the last quarter. Notably, shorter PnR actions, within four seconds post-switch, proved most efficacious. Offensive tactics predominantly capitalized on exploiting speed and size mismatches, with size mismatches demonstrating notable effectiveness. Ball handlers emerged as the primary choice for concluding PnR actions post-switch. These findings offer valuable perspectives on optimizing PnR strategies against switching defenses in basketball.